Evaluation of varying doses of magnesium as an adjuvant to ropivacaine in supraclavicular brachial plexus block - Samuel George,; Karthick Raj A, (Asian Journal of Medical Sciences, 2024)
Background: Peripheral nerve blockade is a crucial component of comprehensive anesthetic care, providing effective analgesia with fewer side effects than opioids and other oral analgesics. Aims and Objectives: This study investigated the effectiveness of a magnesium adjuvant in an ultrasound-guided supraclavicular brachial plexus block to determine the minimum dose required for the desired effects. Materials and Methods: This prospective, double-blind, and randomized controlled study included 90 patients scheduled for elective upper limb orthosurgery at GTMCH. The 90 patients were divided into three groups: A, B, and C. Each group received 21.5 mL of the test drug, with A receiving ropivacaine and normal saline, B receiving ropivacaine and magnesium, and C receiving ropivacaine and magnesium. Results: There was a significant difference in Group A between the onset of sensory and motor blockade in Groups B and C. There was a significant difference in Group A between the duration of sensory and motor blockade in Groups B and C, but no significant difference was observed between Groups B and C. The visual analog scale score varied from 0 to 6 in Group A and from 0 to 5 in Groups B and C. It was found to be significant only from the 7th to 10th h. There was a significant difference in Group A between Groups B and C in 1st rescue analgesia post-operatively and the number of rescue injections in the first 24 h, but no significant differences was observed between Groups B and C. Conclusion: Both 100 and 150 mg magnesium sulfate with 0.5% ropivacaine in supraclavicular blocks prolonged the blockade duration and reduced analgesic needs.